In Vitro Fertilization Following Short In Vitro Maturation versus Intracytoplasmic Sperm Injection: A Comparative Study of Fertilization Outcomes in Sibling Oocytes from Women with Varying Stages of Endometriosis - Marzieh Derakhshan; Samaneh Ghasem Sepro; Maryam Derakhshan; Elham Naghshineh; Minoo Movahedi; Hatav Ghasemi Tehrani; Ensieh Salehi (Clinical and Experimental Obstetrics & Gynecology, 2025)
Background: Endometriosis, a common cause of infertility, adversely impacts both the quality and quantity of oocytes and embryos, with increasing severity negatively influencing assisted reproductive technology (ART) outcomes. This study aims to elucidate and compare the efficacy of two fertilization methods: conventional in vitro fertilization (IVF) following short in vitro maturation (IVM) versus intracytoplasmic sperm injection (ICSI) in patients with varying stages of endometriosis. Methods: In this retrospective study, a total of 134 infertile patients with endometriosis undergoing IVF-ICSI treatment were included. The patients were classified into two groups based on the stage of endometriosis: Stage I–II (n = 79, Group 1) and stage III–IV (n = 55, Group 2). Within each group, participants underwent ART treatments in which sibling oocytes were randomly assigned to either conventional IVF following a short IVM period or the ICSI group. The primary outcomes—fertilization rate, embryo formation rate, and the proportion of high-quality embryos—were assessed and compared between subgroups using the Mann-Whitney U test. Results: Among patients with stage I–II endometriosis, no significant differences were observed between the IVF following short IVM and ICSI subgroups regarding fertilization rate (70 vs. 73, p = 0.543), embryo formation rate (86 vs. 90, p = 0.444), or high-quality embryo rate (67 vs. 71, p = 0.570). Similarly, in the stage III–IV endometriosis group, fertilization rate, embryo formation rate, and the proportion of top-quality embryos on day 3 did not differ significantly between the two subgroups (p > 0.05). Conclusions: Our findings indicated that conventional IVF following a short IVM period yielded comparable outcomes to ICSI in patients with varying stages of endometriosis. Therefore, conventional IVF following a short IVM period may be considered an effective and less invasive fertilization approach for the management of endometriosis-associated infertility.